(untitled) (Journal of Information Technology and Digital World, 2023)
With the ability to improve their perspective of the environment and give useful information and support, augmented reality (AR) has the ability to be extremely helpful for people with disabilities. It is an interactive experience that uses perceptual data produced by computers to enrich the actual environment. Augmented reality uses software, applications, and hardware like AR glasses to superimpose digital material on actual settings and objects. This study article explains how augmented reality benefits persons who are blind or visually impaired, as well as the tools and materials that are utilised for them. This study also discusses a few technologies that will be combined with augmented reality to reach higher levels in the future.